Qubit decoherence from two-level fluctuators –– A numerical and analytical exploration - Chong, Geraldine Kah Min (Nanyang Technological University, 2024)
In solid-state environments, qubit operations are susceptible to charge noise. It couples to the detuning and tunnel coupling parameters in the qubit, which become significant contributors to decoherence, therefore emphasizing the need to better characterize noise in qubits for achieving high-fidelity qubit gate operations. Many previous studies of charge noise go on a few assumptions, namely: (1) It is Gaussian- distributed, which results in qubit decoherence following a Gaussian decay, and (2) it is dominant in the detuning parameter, with noise in the tunnelling parameter taken to be negligible due to it being several orders of amplitudes smaller. While these are good approximations, studies have found that certain situations arise whereby charge noise has a non-Gaussian distribution, or in which noise in the tunnelling parameter dominates over noise in the detuning. In this thesis, we adopted a more general approach to studying noise by making fewer assumptions about noise and starting from the simplest noise model of a two-level fluctuator. We implemented numerical simulations of qubit decoherence due to noise modelled from two-level fluctuators, which are a source of charge noise. Further analysis of the decoherence results was also performed, and to better characterize the obtained results, we derived analytical expressions for the qubit state, r(t), and explored an extended parameter space.